A hybrid reference pulse width modulation technique for binary source multilevel inverter - Vijayakumar Arun; N M G Kumar; Natarajan Prabaharan (Institute of Advanced Engineering and Science, 2022)
The article presents a seven-level reduced switch asymmetrical multilevel inverter with two different methods of pulse width modulation (PWM) techniques. Phase disposition (PD) PWM and hybrid variable-frequency phase disposition PWM (HVFPD-PWM) are the two different PWM methods for making the quality of output voltage waveform. In the first method, the unipolar sine reference with triangular carriers is used. In the second method, the hybrid unipolar reference (sinusoidal with trapezoidal) is proposed with variable frequency carriers to generate the switching pulses for asymmetric multilevel inverter (MLI). The main objective of this proposed method is to reduce the total harmonic distortion in the output voltage waveforms. A comprehensive comparison of the proposed HVFPD-PWM and the conventional PD-PWM with asymmetrical seven-level inverter is presented to show the enriched performances of the proposed method. The performance and viability of the suggested PWM are evaluated through simulation and experimental results using an asymmetrical seven-level inverter. The total harmonic distortion for the proposed PWM method (16.95%) is significantly reduced as compared with the conventional PWM method (18.01%) at the modulation index of one.